Genetic differentiation of Malaysian oaks by microsatellite markers - Pung, Chai Chin (2001)
A combination of nuclear and chloroplast micro satellite DNA have been used to investigate the levels and pattern of variability in Malaysian oaks. This study focussed on Quercus sp., which is the largest and the most widely distributed genus in the family Fagaceae. In the nuclear microsatellite study, four sets of microsatellite primers developed for Quercus sp. (Dow et al., 1995; Steinkellner et atl., 1997a; Isagi and Suhandono, 1997; Kampfer et al., 1998) were tested. Based on the analysis, more than 35% of the 61 primers tested resulted in interpretable amplification products. Twenty microsatellite primers were used to estimate the genetic diversity among distributions of Quercus sp. These selected primers were also used in three other genera from the same family namely, Lithocarpus, Castanop sis and Triganoba/anus. The results showed that these microsatellite loci are conserved across different genera. Four primers, QpZAG9, QrZAG20, QrZAG31 and QrZAG 108 gave interpretable peR products for all the samples studied from the four genera. None of the micro satellite loci is monomorphic in all the species studied. The number of alleles per microsatellite locus varied from 2 to 20. On the average, 11.85 alleles per locus were observed. The mean value of gene diversity ranged from 0.0141 at locus QM50-3M to 0.6494 at locus QpZAGl15 with a mean of 0.3162. The highest mean gene diversity (Ho) for all loci was 0.4290, which was observed in Q. lineata whereas the lowest flo was found in Castanop sis sp. The genetic differentiation among the species was estimated as Fst = 0.6705. Three dendrograms based on Nei's genetic relationship (1978) clustered by the UPGMA method were constructed. The first dendrogram containing four different genera showed that Lithocarpus and Castano pSis are clustered in one group while Triganobalanus is clustered away from Quercus, Lithocarpus and Castanopsis. The second dendrogram showed that the main cluster is subdivided into two major subclusters. The Peninsula species was in one group whereas the Sarawak: species formed another subcluster except for Q. subsericea from Banjaran Lumut. On the other hand, the third dendrogram which clustered individuals of all the species studied showed that all individuals from the same species is clustered together in the same group except for Q. gemelliflora. One unknown individual collected from the Kelabit Highlands is clustered together with Q. sumatrana. The estimates of genetic similarities based on microsatellite markers ranged from 0.0844 to 0.8590 among the different species.